2007
DOI: 10.1159/000099354
|View full text |Cite
|
Sign up to set email alerts
|

De novo Renal Cell Carcinoma in a Kidney Allograft 13 Years after Transplantation: A Case Report and Review of the Literature

Abstract: De novo carcinoma of the renal transplant is a rare but disastrous clinical entity. We report such a tumor developing 13 years after transplantation and describe its clinical presentation, diagnostic approach and therapy. The importance of a surveillance program allowing early detection of tumor developing in the renal transplant is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In a retrospective analysis, Leveridge et al [6] reported 45 RCCs in 3,568 recipients who had renal transplant over a period of 43 years; 39 patients had RCC in the native kidney, while 8 were diagnosed with RCC in renal allograft. The majority of renal allograft tumours are diagnosed incidentally when a biopsy or radiological investigations are performed for other clinical indications [10]. The interval between transplantation and allograft tumour diagnosis ranges between 2 and 258 months (mean 56); early detected tumours most likely represent donor-derived tumours [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis, Leveridge et al [6] reported 45 RCCs in 3,568 recipients who had renal transplant over a period of 43 years; 39 patients had RCC in the native kidney, while 8 were diagnosed with RCC in renal allograft. The majority of renal allograft tumours are diagnosed incidentally when a biopsy or radiological investigations are performed for other clinical indications [10]. The interval between transplantation and allograft tumour diagnosis ranges between 2 and 258 months (mean 56); early detected tumours most likely represent donor-derived tumours [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…4 A review of the current literature identifies 4 cases of multicentric RCC. 5,6 Recurrence of IgA nephropathy after kidney transplant is common, while development of a tumor on the allograft is anecdotal. However, to date, no data exist in the literature regarding the presentation of both pathologies after 25 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time lapse between kidney transplantation and de novo RCC in the allograft varies between 3 and 17 years [5,9,10] (current case: 13 years). CT scan and arteriography, conventional ultrasonography, percutaneous targeted renal biopsy and magnetic resonance imaging (MRI) are the most commonly described diagnostic tools in the literature [5,11,12].…”
Section: Discussionmentioning
confidence: 99%